Health surveillance of workers in indoor environments. Application of the Italian version of the MM040/IAQ questionnaire - Magnavita, Nicola (La Medicina del Lavoro, 2014)
Aims: To test the efficacy of the Italian version of a questionnaire used for the health surveillance of workers operating in confined spaces. Method: The Italian version of the Swedish MM040/Indoor Air Questionnaire was used to collect information on ailments and symptoms related to the indoor environment of 28 workplaces. 4,029 workers took part in the study. Results: For 23.1 % of respondents, the most frequent environmental problem concerned fluctuations in  temperature. For 12.7% of respondents, the commonest work-related symptom was fatigue. Women reported indoor air problems and work-related symptoms more often than men. Allergic subjects reported environmental problems and work-related symptoms more often than non-allergic workers. A significant correlation was found between environmental discomfort and the presence of symptoms. Conclusions: Ailments and work-related symptoms were common in indoor workers, regardless of the presence of collective disorders such as the “sick building syndrome” (SBS).The questionnaire used in this study proved  valuable in helping the occupational health physician to monitor the health of indoor workers. The data collected can provide a reference point for the medical surveillance of workers operating in confined spaces.